Analisis Pemasaran Kelapa di Kecamatan Tanjung Tiram Kabupaten Batubara - Rahmadani Eldiyus; Tumpal HS Siregar; Syaifuddin Lubis (JURNAL AGRICA, 2018)
Tanjung Tiram District is the central areas and the potential for development of coconut commodities because of the natural conditions. The purpose of the study was to determine the coconut marketing channel system, to know the marketing margin on each marketing channel and to determine the level of coconut marketing efficiency. This research is quantitative descriptive by survey method. The research instruments used the interviews and questionnaires. The respondents in the sample used by 80 coconut farmers at Tanjung Tiram District of Batubara Regency. The result of study shows that the most small marketing margin at channel 3 (coconut farmer - retailer - consumer) of Rp. 700/piece of coconut, while the most of marketing margin at channel 2 (coconut farmer - wholesaler - consumer) and channel 5 (coconut farmer - trader - merchants of the city - town factory or retailer - consumer). The conclusion of this study is there are 5 types of coconut marketing channels at Tanjung Tiram District. In terms of the coconut marketing margin that channel 3 most efficient compared  to channel 1, 2, 4 and 5. The farmers choose the channel 1, channel 2, channel 4 and channel 5 even buy coconut at a price lower than the channels 3 because of the four marketing channels to absorb any coconut production whenever farmers at harvest time. Keyword : coconut, traders, marketing